Reclaiming domestic space; Decolonial feminism and women’s sovereignty in Southeast Asia and beyond within the context of artistic practice - Swastika, Alia (Wacana, Journal of the Humanities of Indonesia, 2023)
Contemporary art practices have developed expansively over the global stage with the development of big international exhibitions, including those held in museums or biennales and festivals. In the last decade, the global art world has witnessed the contestation of powers among institutions and art practitioners generated by massive movements such as Occupy Movements, Arab Springs, Black Lives Matter, which has shifted the positionalities of artists and arts in the Global South. This shift also encourages discussions on decoloniality in the art system and art history, including how to centralize the issue of gender equality. Southeast Asian women artists have expanded their practices to show their individual world views, and touch upon political and ideological contexts revealing common urgencies on such issues as ecology, history, spirituality, and humility. This essay discusses art works created by women artists in Southeast Asia presented as part of the Biennale Jogja Equator (BJE) series in the period 2011 to 2021. This has provided artists with possibilities to engage in critical conversations and experiences, usually the preserve of the male-dominated sphere. By looking into these projects, the wide range of the shared trauma of violence, war, and colonialism, ecological damage, and lost livelihoods, to the pilgrimage towards the inner-self, have been juxtaposed and interwoven to create an imagination of collective futurism.